Coach leadership behavior and achievement goal orientation in relation to athlete engagement: the dual mediating role of basic psychological needs - Li, Kaixin; Cui, Zhibu; Wang, Tong; Li, Zhihua; Yang, Chengbo (Frontiers in Psychology, 2025)
ObjectiveThis study explored how coach leadership behavior, achievement goal orientation, and basic psychological needs affect athlete engagement.MethodsBased on self-determination theory, this study examined the influence of coach leadership behavior and achievement goal orientation on athlete engagement, as well as the mediating effect of basic psychological needs. The study utilized established scales, including the Leadership Behavior Scale for Coaches-15 (LSS-15), the Achievement Goal Questionnaire for Sport (AGQ-S), the Athlete Engagement Questionnaire (AEQ) and the Basic Psychological Needs Questionnaire (BPNQ).ResultsA total of 351 valid questionnaires were analyzed. The results found that (1) basic psychological needs, coach leadership behavior, and achievement goal orientation can predict athlete engagement, and a correlation exists between them; (2) basic psychological needs play a double mediating role in coach leadership behavior and athlete engagement, achievement goal orientation, and athlete engagement. Coach leadership behavior and basic psychological needs have a chain mediation mechanism between achievement goal orientation and athlete engagement. Achievement goal orientation and basic psychological needs have a chain mediation mechanism between coach leadership behavior and athlete engagement; (3) after model testing and model difference comparison. The effect of the chain model based on the coach leadership behavior is more significant, indicating that the plasticity of the coach leadership behavior is the strongest.ConclusionThese findings analyze the relationship between coach leadership behavior, achievement goal orientation, basic psychological needs, and athlete engagement to optimize coach leadership behavior, guide the setting of reasonable achievement goal orientation, meet basic psychological needs, improve athlete engagement, and provide practical guidance for targeted intervention measures.